Immunodiagnosis of Systemic Lupus Erythematosus (SLE) in a tertiary care hospital - Ragunathan, Latha; Chidambaram, Anandi; Kannaiyan, Kavitha; N, Chidambaram (Annals of Pathology and Laboratory Medicine, 2020)
Objectives To diagnose patients with Systemic lupus erythematosus clinically and compare various immunological tests available to detect their specificity and sensitivity of the various parameters employed. Methods It was a hospital-based cross-sectional study. All patients satisfying the revised American College of Rheumatology criteria (1982) for SLE were included in the study over a period of 3 years. A total of two hundred and four individuals were included. The patients were divided into three groups- (Group I- Confirmed SLE patients-32, Group II- Incomplete SLE patients- 60, and Group III -patients with other autoimmune disorders- 42) and 70 persons were included as controls. Results Patients were divided into three groups I, II, III and their clinical & laboratory features were compared. Females (90.6%) were more affected than males (9.4%) and 69% were in the age group of 20-40 years. The average age of onset of disease was 24.4 years. Predominant clinical features were arthritis (81.25%), skin rashes (72%), myalgia (68.75%), alopecia (68.75%), fever (65%) and oral ulcers 18(56.25%). Anti-ds-DNA test and ANA test were positive in all the patients and the anti-DNP test was positive in 59.3% patients. Females were more affected (81.7%) than males (18.3%). 85% were between 21-50 years The average age of patients was 30.16 years with a range of 10-70 years. Patients were regularly followed up and 32 patients (26.67%) developed complete SLE. The most common manifestations were arthritis (88.3%), fever (43.3%) skin rashes (68.3%). 10.34% of ILE patients developed full SLE and all were females. Average age of disease onset was 24years. Anti-ds-DNA antibodies was detected in 28 patients (23.4%), ANA in (25%) patients and Anti-DNP antibodies in 12 (10%) patients. Females (81%) were affected than males (19%). 86% were between 21-50 years. The average age of patients was 33.24 years. The predominant clinical features were arthritis (78.6%) and myalgia (76.2%). Anti-ds-DNA antibodies were detected in 6%, ANA in 35.7% patients & Anti-DNP antibodies in 3.6%. Antibodies to ds-DNA were present in low titers in this group. Conclusion A clear separation between SLE and other autoimmune disorder was found with the anti-ds-DNA test. It has a high specificity for the differential diagnosis of SLE. Our study, comparing three assays with respect to their ability to predict disease activity, indicated that ds- DNA ELISA is the best method.